2013
DOI: 10.1016/j.esr.2012.12.003
|View full text |Cite
|
Sign up to set email alerts
|

System and market integration of wind power in Denmark

Abstract: Denmark has more than 10 years of experience with a wind share of approximately 20 per cent. During these 10 years, electricity markets have been subject to developments with a key focus on integrating wind power as well as trading electricity with neighbouring countries. This article introduces a methodology to analyse and understand the current market integration of wind power and concludes that the majority of Danish wind power in the period 2004-2008 was used to meet the domestic demand. Based on a physica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 50 publications
(16 citation statements)
references
References 53 publications
1
15
0
Order By: Relevance
“…Hong et al [180] and Cerovac et al [198] use EnergyPLAN simulations to point towards the importance of flexible power plants to accommodate the fluctuating nature of RES; in these cases wind power in Croatia and China. This is in line with the logic of Lund et al's [213] analyses of excess power generation in Denmark.…”
Section: Findings From Energyplan Simulationssupporting
confidence: 78%
“…Hong et al [180] and Cerovac et al [198] use EnergyPLAN simulations to point towards the importance of flexible power plants to accommodate the fluctuating nature of RES; in these cases wind power in Croatia and China. This is in line with the logic of Lund et al's [213] analyses of excess power generation in Denmark.…”
Section: Findings From Energyplan Simulationssupporting
confidence: 78%
“…The incentive for biogas upgrading relate to the larger scale transition of energy systems to renewable energy that is presently pursued by many countries. When releasing the energy supply from fossil fuels, the nature of the energy system changes towards a high share of fluctuating energy from wind and solar power and towards a high dependency on biomass resources (Danish Energy Agency, 2014a ;Lund et al, 2011). With respect to the role of biogas in the energy system, this creates economic and environmental incentives for biogas upgrading.…”
Section: The Incentives and Feasibility Of Biogas Upgradingmentioning
confidence: 99%
“…As the market conditions in Denmark have proven their ability to integrate large shares of intermittent RES [1], these market conditions are perceived as representative for market systems with a high integration of intermittent RES. Likewise, Denmark has a relatively high amount of DH plants with flexible distributed CHP units.…”
Section: Methodsmentioning
confidence: 99%
“…The increased capacity of intermittent renewable energy sources (RES) increases the need for flexibility in the energy system [1,2]. Lund et al [3] found that district heating (DH) should have an increased interaction with the electricity system in future sustainable energy systems, as DH can help integrate flexible solutions and improve the energy efficiency of the system.…”
Section: Introductionmentioning
confidence: 99%